Food Wars: the global battle for mouths, minds and markets. 2. ed. London: Earthscan, 2015. 296p. - Marielen Priscila Kaufmann (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2020)
The second edition of Tim Lang and Michael Haesman's Food Wars: The Global Battle for Mouths, Minds and Markets, published in 2015, is a book that brings together important elements for the discussion of agrifood policies in the globalized world. Furthermore, the review aims to discuss some of the elements about the modern agrifood system configuration, as well as to present the authors' overview about the environmental and economic world sustainability, based on food. The publication discusses public health, environmental issues, regime of production, storage, distribution, global markets and their arrangements, the perspective of consumers in the modern world and global food policies, contextualized in nine chapters, which portray the panorama of food problems in the world. Moreover, the authors' great contribution to scientific research related to the Food Sociology is the dialogue between themes such as environmental sustainability, the search for health and quality of life and food.